THE ROLE OF TEACHERS IN DEVELOPING STUDENTS’ CRITICAL THINKING SKILLS - Rahimjanova Muqaddas Dilmurod qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: In the rapidly changing landscape of global education, the development of students’ critical thinking skills has emerged as a vital goal for educators worldwide. Critical thinking allows learners to analyze information, solve complex problems, and make rational decisions in various contexts. This thesis explores the central role of teachers in cultivating critical thinking among students. It examines theoretical perspectives, pedagogical strategies, and empirical findings that highlight how teachers can create learning environments conducive to critical inquiry. Drawing on the works of Dewey, Vygotsky, Brookfield, and Paul & Elder, the study emphasizes that teachers act not merely as transmitters of knowledge but as facilitators of reflection, questioning, and reasoning. The research also underscores the importance of teacher competencies such as reflective practice, metacognitive awareness, and the use of problem-based and inquiry-based learning methods. Ultimately, the paper argues that teachers’ commitment to fostering intellectual curiosity and open-mindedness is the cornerstone of developing students’ critical thinking abilities.